Long-term outcomes of Japan-specific dosage of rivaroxaban in high-risk patients with non-valvular atrial fibrillation: analysis from the XAPASS. (25th November 2020) - Ikeda, T; Ogawa, S; Kitazono, T; Nakagawara, J; Minematsu, K; Miyamoto, S; Murakawa, Y; Iwashiro, S; Hayashi, Y; Okayama, Y; Sunaya, T; Sato, S; et al.
Abstract: Background: XAPASS is a real-world, prospective, single-arm, observational study conducted as a post-marketing surveillance mandated by the health authority in Japan. Nowadays, direct oral anticoagulant therapy using factor Xa or thrombin inhibitor has been the standard of care for patients with non-valvular atrial fibrillation (NVAF) to prevent ischemic stroke. However, the clinical impact of reduced dosage (approved dose of 15 or 10 mg once daily in Japan is relatively reduced compared to global dosage) factor Xa inhibitor rivaroxaban in high-risk patients remains unclear. Purpose: The present sub-analysis of XAPASS was carried out to assess long-term safety and effectiveness of reduced-dose rivaroxaban in high-risk NVAF patients for bleeding and thromboembolism. Methods: All patients with NVAF who were newly started on rivaroxaban were eligible for surveillance. The principal safety outcome was a composite of major and non-major bleeding events, and the primary effectiveness outcome was a composite of ischaemic stroke, haemorrhagic stroke, non-central nervous system systemic embolism (non-CNS SE), and myocardial infarction (MI). In this present sub-analysis, high-risk patients were defined as those who had two of the following three risk factors: elderly (≥75 years old), low body weight (≤50 kg), and renal impairment (CrCl <50 mL/min). Results: In total, 11, 308 patients were enrolled between April 2012 and June 2014 from 1, 419 hospitals, and overall data were analysed from 10, 664 patients from whom data were collected. Among them, 3, 694 patients matched the criteria for the high-risk patients defined in this sub-analysis, and 6, 970 patients did not match the criteria (non-high-risk patients). The mean treatment duration was 791±673 days in the high-risk patients and 944±709 days in the non-high-risk patients. Mean patient age was 80.9±5.5 years and 69.0±9.0 years at baseline, respectively. Mean CHADS2 score was 2.8 and 1.8, and CHA2DS2-VASc score was 4.4 and 2.9, respectively. The rates of CHADS2 component comorbidities were lower in the non-high-risk patients except for diabetes mellitus. The incidence rates of any bleeding, major bleeding, and the primary effectiveness outcomes were 4.8, 1.6, and 2.1%/patient-year in the high-risk patients. The incidence rates of these clinical events in the non-high-risk patients were 3.3, 0.9, and 1.0%/patient-year, respectively. Conclusions: Incidence rates of long-term bleeding and thromboembolism were higher in the high-risk patients than in the non-high-risk patients. However, the rates of these outcomes using the Japan-specific reduced dose were not so high. Furthermore, the balance between safety and effectiveness outcomes was within an acceptable range. The present study provides useful information for physicians to stratify high-risk patients using the reduced dose in daily clinical practice. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Bayer Yakuhin Ltd.